Rapid 3d-imaging of semiconductor chips using thz time-of-flight technique - Yim, Jong Hyuk; Kim, Su Yeon; Kim, Yiseob; Cho, Suyoung; Kim, Jangsun; Ahn, Yeong Hwan (Applied Sciences (Switzerland), 2021)
In this study, we developed a rapid three-dimensional (3D) time-of-flight imaging tool for inspection of packaged semiconductor chips, using terahertz (THz) time-domain spectroscopy tech-niques. A high-speed THz system based on the optical sampling by cavity tuning technique is in-corporated with a 2-axis galvano scanner to deliver a scanning speed of more than 100 Hz/pixel with a signal-to-noise ratio larger than 20 dB. Through the use of the Hilbert transformation, we reconstruct the 3D structure of the packaged chip in a nondestructive manner. Additionally, the use of frequency-selective imaging allows us to manipulate image resolution; the higher resolution was obtained when monitored using the higher frequency component. Further, using phase information, we were able to detect and identify defects in the packaged chip, such as the delamination area and epoxy-rich regions.
Keywords: Packaged chip; Terahertz imaging; Time-of-flight